Selective Mineralization of Tough Hydrogel Lumens for Simulating Arterial Plaque . Issue 1 (4th November 2016) - Lao, Lihong; Robinson, Sanlin S.; Peele, Bryan; Zhao, Huichan; Mac Murray, Benjamin C.; Min, James K.; Mosadegh, Bobak; Dunham, Simon; Shepherd, Robert F.
Abstract : This paper demonstrates progress of fabricating artificial arteries (phantoms) that mimic plaque buildup. Hydrogel lumens are molded using tough polyacrylamide with regions selectively mineralized with calcium phosphate. By tuning the degree of mineralization such as calcium concentration ([Ca 2+ ], 0.4–2 M), and crystallization time ( t c, 1–4 weeks), the authors control the extent of lumen occlusion. These occluded lumens significantly reduce pressure (Δ P ≈ 7.79 kPa) during fluid flow compared to the non‐calcified lumens (Δ P ≈ 1.24 kPa). Additionally, image, chemical analysis, and compressive mechanical tests are performed to determine the effect of synthesis conditions on the composite's mechanical properties. For comparison to real arteries, the authors also present dynamic mechanical analysis of human aortic tissue. Abstract : Hydrogel lumens are molded using tough polyacrylamide with regions selectively mineralized with calcium phosphate to fabricate artificial coronary arteries (phantoms) that mimic plaque buildup. The extent of lumen occlusion can be controlled under different conditions. These synthetic, occluded lumens significantly increase the stiffness, and reduce pressure (up to ≈ 7.79 kPa) during fluid flow compared to the non‐calcified hydrogels (≈1.24 kPa).